Morphometric Parameters of Epididymis of Rats of Different Ages Receiving Radiation (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In this article, the morphometric parameters of the epididymis of rats of different ages that received radiation were examined. It has been proven in the experiment that the radiation, which has a negative effect on the morphological structures of the epididymis, has a significant effect on all the morphometric indicators of this organ. Chronic radiation sickness affects the vasculature of the epididymis and convoluted tubules, where the diameter of arterioles and venules, as well as the diameter of the convoluted tubules, is further reduced by radiation.